The way of photonic crystal formation in A³B³ and A²B⁶ semiconductors - Kamuz, A.M.; Oleksenko, P.Ph.; Kamuz, O.A.; Kamuz, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
It is shown that under influence of irreversible gigantic modification in monocrystalline A³B³ and A²B⁶ semiconductors, local areas with the highly changed refractive index are created. It was shown that a complex refraction index of CdS, CdTe and GaAs semiconductor samples after their modification was essentially changed. For example, the complex refraction index of CdS samples was changed from the magnitude N = 2.75 + i2.8113 up to the magnitude N1 = 1.9 + i0.035. In addition, the real and imaginary parts of a complex refraction index of CdS decrease, accordingly, by 0.85 and 2.7763. And its absorption index was 80-fold decreased. The theoretical analysis of experimental results has shown that quantum dots and quantum wires are responsible for such huge changes of the refractive index, which arise in modified areas of samples. It was shown that boundaries between modified and non-modified areas of the sample stretch down to the depth not less than 11mm. It was shown that photon crystals with one-dimensionality and two-dimensionality can be effectively formed for visible and ultra-violet ranges without using the complex lithographical technique.